Mechanisms of Phytoremediation by Resveratrol against Cadmium Toxicity - Barbara Mognetti; Francesco Franco; Chiara Castrignano; Patrizia Bovolin; Giovanni Nicolao Berta (MDPI AG, 2024)
Cadmium (Cd) toxicity poses a significant threat to human health and the environment due to its widespread occurrence and persistence. In recent years, considerable attention has been directed towards exploring natural compounds with potential protective effects against Cd-induced toxicity. Among these compounds, resveratrol (RV) has emerged as a promising candidate, demonstrating a range of beneficial effects attributed to its antioxidant and anti-inflammatory properties. This literature review systematically evaluates the protective role of RV against Cd toxicity, considering the various mechanisms of action involved. A comprehensive analysis of both in vitro and in vivo studies is conducted to provide a comprehensive understanding of RV efficacy in mitigating Cd-induced damage. Additionally, this review highlights the importance of phytoremediation strategies in addressing Cd contamination, emphasizing the potential of RV in enhancing the efficiency of such remediation techniques. Through the integration of diverse research findings, this review underscores the therapeutic potential of RV in combating Cd toxicity and underscores the need for further investigation to elucidate its precise mechanisms of action and optimize its application in environmental and clinical settings.